DETECTION OF LISTERIA MONOCYTOGENES IN RAW MILK AND ABORTED COW CASES AT SALAHUDEEN PROVINCE - Noomi, B. S.; Anwar, Sh. A.; Salih, S. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Listeria monocytogenes is a pathogen that causes infectious diseases in animals. It is one of the causal agents causing abortion in infected cows. This study was conducted to detect listeria monocytogenes in aborted cows. Also to estimate the role of the milk in the distribution of the pathogen by detecting the bacteria in milk of aborted cows as well as in raw milk from the market of Salahudeen province. The study includes 46 aborted cows from which 46 milk samples were taken to detect the causative agents. Also 38 vaginal swabs were taken from the same aborted cows and 8 samples from fetuses. 30 raw milk samples were also taken from market at Salahudeen province. The results showed that Listeria monocytogenes were detected in 5 (13.1%) of vaginal swabs, 2 (25%) of aborted fetuses, 13 (28.26%) in milks from aborted cows, and 9 (30%) of raw milks. The isolated pathogens were screened for the presence of 3 virulence factors; InlJ, InlA, and HIY. The results showed that theses virulence genes were found in the majority of the isolates and the isolation rate ranged between 75%-100%. The study concluded that milk is one of the main sources for the pathogen spreads to other animals.